The application of transdermal buprenorphine in the treatment of chronic cancer pain - Ciałkowska-Rysz, Aleksandra; Kaźmierczak-Łukaszewicz, Sylwia; Gottwald, Leszek (Medycyna Paliatywna/Palliative Medicine, 2009)
Introduction: Buprenorphine is a semi-synthetic opioid which has interesting physicochemi- cal properties. Due to its beneficial pharmacokinetic profile, it is becoming widely used in the treatment of severe cancer and non-cancer pain. Aim of the study: To evaluate the effectiveness and safety of transdermal buprenorphine in the treatment of cancer pain. Material and methods: This research was not invasive since it was based on the analysis of medical documentation of 74 patients suffering from cancer pain, treated in the Regional Centre of Oncology in Lodz and in the home hospice. Buprenorphine in the dose range of 35-105 µg/hour was applied. In the complementary treatment, other medicines having an analgesic effect were used in accordance with recommendations. Analgesic effects were assessed on the basis of a 3-point verbal evaluation scale (good effect, mediocre effect and no effect). Obtained results were analyzed statistically. Results: Pain relief was observed in all patients. The effect of buprenorphine was described as good in 60 patients (81.08%) and as mediocre in 14 patients (18.92%) (p < 0.001). Constipation was observed in 21 patients (28.38%), nausea in 5 patients (6.77%), vomiting occurred in 2 patients (2.70%) and dermal allergic reaction in 3 patients (4.05%). A tendency toward plaster unsticking occurred in one patient with hyperhidrosis (1.36%). No other complications associated with the applied therapy were observed. Conclusions: The treatment of the study group with transdermal buprenorphine was associated with good pain control. This drug was well tolerated; side-effects were sparse and not intense. No additional side effects induced by simultaneous use of other analgesics were observed.